PENGARUH KONSENTRASI MIKROORGANISME LOKAL DARI LIMBAH TOMAT DAN LIMBAH AIR KELAPA TERHADAP PERTUMBUHAN TANAMAN CABAI (Capsicum annum L.) - EFRIDA PIMA TAMBUNAN (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2017)
The objective of this research is to know the effect of local microorganism solution (MOL) from tomato waste and coconut water waste to chili plant growth (Capsicum annum L.) and to know the MOL concentration from tomato waste and coconut water waste which give the best influence to the growth of chilli plant (Capsicum annum L .). This research was conducted at Jl. Sidomulyo Gg. Sahabat, Pasar 7, Helvetia Medan, took place from August to December 2017. This study used a Completely Random Design (RAL) consisting of one factor with 4 treatments ie M0 = Control (without treatment), M1 = 5 ml MOL / L water, M2 = 10 ml MOL / L water, M3 = 15 ml MOL / L water, with 5 replications. Parameters observed were; plant height (cm), number of leaves (strands), and wet weight of plant (gram). The results of this research indicate that permeian MOL of tomato waste and coconut water waste have an effect to increase the growth and productivity of pepper plant. The most effective concentration of MOL tomato waste and coconut water waste to increase the growth and production of chili is 15 ml / L.